Pengaruh Penerapan Standar Akuntansi Negara Terhadap Kualitas Pelaporan Keuangan Pada Rekening Daerah Kementerian Agama Provinsi Lampung - Alayubi, Fandhuta Dhafa; Komariah, Rizka; Susanto, Rindang (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
Financial reports of exceptional quality at the Regional Office of the Ministry of Religion in Lampung Province (Kanwil Kemenag Lampung) demonstrate the accountability and effectiveness of regional managers. These reports showcase their commitment to responsible resource management and demonstrate their responsiveness to financial accountability. This study, conducted from March to April 2022, employed a combination of questionnaires and face-to-face interviews with key stakeholders to gather primary data. The research concludes that implementing government accounting standards within Kanwil Kemenag Lampung has yielded highly beneficial results. The quality of financial reporting has been significantly elevated, indicating responsible stewardship of public resources. This analysis, utilizing simple linear regression conducted through SPSS, further reveals a strong positive correlation between the effectiveness of applying government accounting standards and the overall quality of government financial reporting. The study's sample included 30 employees from the regional office's finance department and 10 additional multipliers. Statistical tests, including a T-test, revealed significant differences in the effectiveness of implementing government accounting standards. The T-statistic of 33.968, with a p-value of 0.021 (significantly lower than the 0.05 threshold), confirms a statistically significant impact. Additionally, the regression coefficient of 0.930 underscores a strong positive correlation between the two variables. In essence, this research highlights the positive impact of implementing government accounting standards on the financial reporting quality and accountability of regional offices. By ensuring responsible resource management and effective financial reporting practices, Kanwil Kemenag Lampung exemplifies a model for other regional offices to emulate.